Global Research Trends on Emergency Medical Technicians: A Bibliometric Analysis (2015-2025) - Misbahuddin Azis; Shanti Wardaningsih (Universitas Malahayati, 2026)
ABSTRACT Emergency medical technician (EMT) is a frontline responder trained to provide basic emergency care, including CPR, bleeding control, airway management, and patient assessment. Despite growing research, no comprehensive bibliometric analysis has been conducted on this topic. This study systematically maps the scientific landscape, research trends, and thematic structures of emergency medical technician, identifying clusters, gaps, and future directions. A bibliometric analysis of publications in the Scopus database was performed, with visualization, co-occurrence, and trend analyses conducted using VOS viewersoftware (version 1.6.20). From 6,459 relevant publications indicated increasing research activity despiteperiodic fluctuations, Five thematic clusters emerged: (1) EMT, (2) emergency health service, (3) emergency medical service, (4) emergency medical technician, and (5) rescue personnel. Overlay visualisation revealed a recent research shift (2015–2025) toward paramedic personnel, and allied health personnel. China was the country with leading contributor and The most cited work was Bulger et al. (2019), cited 161 times. This bibliometric study on emergency medical technician highlights priorities in The role of Emergency Medical Technicians (EMTs) in the global healthcare and emergency medical systems, the development and increasing complexity of professional practice, and the growing volume of scholarly publications related to EMTs. The findings offer a reference for future research of understanding of the evolution, structure, and direction of global EMT and offers valuable insights for researchers, educators, practitioners, and policymakers seeking to strengthen emergency medical services worldwide.. Keywords: Bibliometric Analysis, Emergency Medical Technician, Paramedic, Vosviewer.